First record of coexistence between Loxosceles laeta (Araneae: sicariidae) (Nicolet, 1849) and Hadruroides lunatus (Scorpiones: vejovidae) (Koch, 1867) in Peru - Macedo Bedoya, Jehoshua (2024)
This study documents for the first time the coexistence of Loxosceles laeta and Hadruroides lunatus in Peru. The research was conducted at the Universidad Nacional Mayor de San Marcos, Lima, during June 2024. Visual inspection methods and rock lifting were employed to record individuals of both species, measuring the distances between them. Previous observations conducted in 2023 revealed reduced interactions during the summer, suggesting seasonal influences.